2022
DOI: 10.3389/fgene.2022.843269
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Transcriptome Analysis of Stem-Differentiating Xylem Upon Compression Stress in Cunninghamia Lanceolata

Abstract: Compression wood (CW) in gymnosperm brings great difficulties to wood industry using wood as raw materials since CW presents special wood structure and have different physical and chemical properties from those of normal wood (NW). Chinese fir (Cunninghamia lanceolata) is widely distributed in China. However, global transcriptome profiling of coding and long non-coding RNA in response to compression stress has not been reported in the gymnosperm species. In this study, we revealed that CW in Chinese fir exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…The activities of these genes predominantly increased during the SP and decreased in FA. In the context of previous research, it was noted that CW had an increase in not only lignin-related genes (such as PAL, C3H, 4CL, CAD, HCT, and CCoAOMT) but also those related to cellulose biosynthesis (such as CSLA) [ 21 , 24 ]. In contrast, our study observed no abundant expression in CW of these genes, with the exception of laccase ( Figure 5 and Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activities of these genes predominantly increased during the SP and decreased in FA. In the context of previous research, it was noted that CW had an increase in not only lignin-related genes (such as PAL, C3H, 4CL, CAD, HCT, and CCoAOMT) but also those related to cellulose biosynthesis (such as CSLA) [ 21 , 24 ]. In contrast, our study observed no abundant expression in CW of these genes, with the exception of laccase ( Figure 5 and Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gymnosperm wood is characterized by high lignin content (25–35%), an HG-type of lignin with more guaiacyl (G) units but a small portion of p-hydroxyphenyl (H) units., whereas angiosperm wood has a lignin content of 15–28%, with a GS-lignin having different proportions of syringyl (S) units [ 22 , 23 ]. It has recently been shown that laccase, responsible for monolignol polymerization, is crucial for lignin biosynthesis in compression wood [ 22 , 24 ]. Lignin-derived fuels have gained popularity in recent years as a technology to produce biofuels from biomass with the potential to reduce dependence on fossil fuels and greenhouse gas emissions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the several TaNAC TFs that bind to the selected TaCKX GFM cis-regulatory sequences, we selected only one TaNAC TF with the highest binding affinity parameters for each selected TaCKX GFM, except TaCKX10-7B (Table 1), for further characterization. Similarly to us, in several studies, including Pompili [35][36][37], other authors have used the plant transcription factor database (PlantTFDB v5.0) to identify transcription factors. The names of the selected TaNAC TFs in the NCBI database were identified as: transcription factor JUNGBRUNNEN 1-like, NAC domain-containing protein 13-like, putative NAC domain-containing protein 94, and protein BEARSKIN-1-like, which bind to the cis-regulatory sites of the TaCKX1-3A, TaCKX2.2.1-3B, TaCKX5-3D, TaCKX9-1B, and TaCKX10-7B TaCKX GFMs, respectively.…”
Section: Tanac Tfs Orchestrate Cis-regulation Of Tackx Gfmsmentioning
confidence: 99%
“…Our previous study showed that MYB2, MYB21, and MYB092 are differentially expressed upon compression stress in Cunninghamia lanceolata (Lamb.) Hook (C. lanceolata) [43]. C. lanceolata, as endemic and evergreen coniferous species, is one of the most important artificial timber forest species in southern China because of its high timber quality and fast growth [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Hook (C. lanceolata) [43]. C. lanceolata, as endemic and evergreen coniferous species, is one of the most important artificial timber forest species in southern China because of its high timber quality and fast growth [43,44]. C. lanceolata is gradually suffering from increased stress, including temperature [45], drought stress [46], and autotoxicity caused by allelopathic toxins such as phenolic acids [47].…”
Section: Introductionmentioning
confidence: 99%